(3EMjGA Ydhe GdOjfs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3eMeO Hf EHQGgje GdTGaYi s)
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg CKfGA cJGH QjGVI GdfaS bhdg (B: (3deG HYK Gddg ehSi hgGQhf YdjgeG GdSdGe Edi aQYhf , bGd (B: (3dG jQhYfceG dHGSg GdPi djS ef GdOfjG , aEf fGUjJg HjOi s
(3BNQgG (B:s
(3adPdc dGjaGQb GdNha hGdMPQ bdhH ChdjGA Gddg GHOkG , afSCd Gddg JYGdi Je cJGH GdZQhQ , hJe Hg cJGH GdZQhQ , hJe Hg QHY GdegdcGJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QHY GdegdcGJs
(3cJHJ HYV GdYfhGfGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJUha hGdBOGH GdTQYjIs